Investment Functions with q in the Presence of Unobserved Persistent Shocks - Kim, Kyoo il; Song, Suyong; Wang, Jiawei (Brooke) (Journal of Financial and Quantitative Analysis, 2026)
Abstract We study the classical relationship between a firm’s investment and q , for which an unobserved persistent shock is an important factor in the investment decision. In our setting, besides the potential measurement problem of q , controlling for the unobserved shock becomes a new challenge. We develop an estimation method that addresses both econometric issues given timing and information set assumptions. Using 16,256 unique public firms in the United States from 1975 to 2021, we find that q remains a significant factor of investment even after controlling for the unobserved shock and measurement error.